DIGITAL TRANSFORMATION OF URBAN TRANSPORT SYSTEMS: CLASSIFICATION OF APPROACHES AND RECOMMENDATIONS FOR UKRAINE - POSTRELKO, YEVHENII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This article explores contemporary approaches to the digital transformation of urban transport systems, focusing on their classification, implementation examples in Ukraine and abroad, and the development of an adaptive model for Ukrainian cities. Based on an analysis of infrastructural, organizational, and digital solutions, the author formulates recommendations for the phased implementation of transport flow management systems utilizing open data, APIs, and visualization tools. The article also proposes criteria for evaluating the effectiveness of such solutions and highlights the role of municipalities, the IT sector, and the public in shaping sustainable urban mobility.
Keywords: web system; public transport monitoring; urban transport; mobility as a service; urban mobility